Driving innovation : intellectual property strategies for a dynamic world - Gollin, Michael A., 1957- (Cambridge University Press, 2008)
How does IP balance the exclusive rights of innovators with public demand for access to their innovations? How can organizations manage IP strategically to meet their goals? How do IP strategies play out on the global stage? Driving Innovation reveals the dynamics of intellectual property (IP) as it drives the innovation cycle and shapes global society. The book presents fundamental IP concepts and practical legal and business strategies that apply to all innovation communities, including industry, non-profit institutions, and developing countries. Further, it draws on the author's broad experience, news headlines, and precedent-setting lawsuits relating to patents, trademarks, copyright, and trade secrets - from biotechnology to the open source movement. General readers and students will welcome the lively overview of this complex topic, while executives and practitioners can gain new insights and valuable approaches for putting ideas to work and navigating within or changing the global IP system to expand innovation.